Promoting Sustainable Rural Livelihoods: a Framework for Managing Multi, Institute Consortia - Sreenath Dixit; B. Venkateswarlu; A.P. Srivastava (Journal of Agricultural Extension Management, 2025)
Watershed development approach has been followed for over three decades to address the complex and diverse development needs of rainfed areas. The challenges of development in these areas demand multidisciplinary and multi institutional approaches. The coming together of institutions having strengths in different areas of watershed development, community mobilization and institutional development as a consortium to implement what are called watershed plus or sustainable rural livelihoods projects is a recent phenomenon. It has become more of a necessity as a result of increasing complexity of development. This paper I traces the evolution of the consortium concept over time, discusses project implementation and institutional frameworks and documents the first hand experiences emanating from out of one such multidisciplinary multiinstitute consortium. Besides, it attempts to deduce the learnings accrued as a result of implementing a large project aimed at improving the livelihoods of the rural poor by a consortium of private, public, and nongovernment organizations.